Progovac, Liliana: Evolutionary syntax. - Putnam, Michael T. (Norsk Lingvistisk Tidsskrift, 2016)
In this monograph, Liliana Progovac (LP) challenges this mainstream assumption in presenting her case for a gradualist, adaptationist approach to the evolution of syntax.